Siah2‐deficient mice show impaired skin wound repair. Issue 3 (29th April 2013) - Musyoka, James N.; Liu, Mira C.P.; Pouniotis, Dodie S.; Wong, Christina S.F.; Bowtell, David D.; Little, Peter J.; Getachew, Robel; Möller, Andreas; Darby, Ian A.
Abstract Hypoxia is associated with the dermal wound healing process and hypoxia signaling is presumed to be crucial for normal wound repair. The Siah2 ubiquitin ligase controls the abundance of hypoxia‐inducible factor‐1 alpha, and loss of Siah2 results in destabilization of hypoxia‐inducible factor‐1 alpha under hypoxia. Utilizing Siah2−/− mice we demonstrate that cutaneous wound healing is impaired in these mice. Wounds in Siah2−/− mice heal slower and are associated with delayed induction of myofibroblast infiltration and reduced collagen deposition. This coincides with delayed angiogenesis and reduced macrophage infiltration into the wounds of Siah2−/− mice. We furthermore demonstrate that primary Siah2−/− dermal fibroblasts have reduced migratory capacities and produce less collagen than wild‐type fibroblasts. Additionally, Siah2−/− fibroblasts showed conserved responses to transforming growth factor‐β at the receptor level (pSmad 2C activation) but reduced responses downstream. Together, our data show, for the first time, that Siah2 is involved as a positive regulator in the wound healing response. Understanding the role of hypoxia signaling in tissue repair and fibrosis and interference with the hypoxia signaling pathway via regulation of Siah2 may provide new targets for clinical regulation of fibrosis and scarring.